Comparison of photosynthetic pigments and phytoplankton assemblages in two types of coastal regions in Southeast Asia-Indonesian Throughflow and river estuary - Wang, Lei; Huang, Hao; An, Lina; Thoha, Hikmah; Bong, Chui Wei; Xiao, Wupeng; Gu, Haifeng (Springer Verlag, 2018)
Water samples were collected in order to study the spatial variation of photosynthetic pigments and phytoplankton community composition in the Lembeh Strait (Indonesia) and the Kelantan River Estuary (Malaysia) during July and August 2016, respectively. Phytoplankton photosynthetic pigments were detected using high performance liquid chromatography combining with the CHEMTAX software to confirm the Chl a biomass and community composition. The Chl a concentration was low at surface in the Lembeh Strait, which it was 0.580–0.682 μg/L, with the average (0.620±0.039) μg/L. Nevertheless, the Chl a concentration fluctuated violently at surface in the Kelantan River Estuary, in which the biomass was 0.299–3.988 μg/L, with the average (0.922± 0.992) μg/L. The biomass at bottom water was higher than at surface in the Kelantan River Estuary, in which the Chl a concentration was 0.704–2.352 μg/L, with the average (1.493±0.571) μg/L. Chl b, zeaxanthin and fucoxanthin were three most abundant pigments in the Lembeh Strait. As a consequence, phytoplankton community composition was different in the two study areas. In the Lembeh Strait, prasinophytes (26.48%±0.83%) and Synechococcus (25.73%±4.13%) occupied ~50% of the Chl a biomass, followed by diatoms (20.49%±2.34%) and haptophytes T8 (15.13%±2.42%). At surface water in the Kelantan River Estuary, diatoms (58.53%±18.44%) dominated more than half of the phytoplankton biomass, followed by Synechococcus (27.27%±14.84%) and prasinophytes (7.00%±4.39%). It showed the similar status at the bottom water in the Kelantan River Estuary, where diatoms, Synechococcus and prasinophytes contributed 64.89%±15.29%, 16.23%±9.98% and 8.91%±2.62%, respectively. The different phytoplankton community composition between the two regions implied that the bottom up control affected the phytoplankton biomass in the Lembeh Strait where the oligotrophic water derived from the West Pacific Ocean. The terrigenous nutrients supplied the diatoms growing, and pico-phytoplankton was grazed through top down control in the Kelantan River Estuary.